Engineered LDH-alginate composite hydrogel columns for selective heavy metal removal - Hao, Hualai (Frontiers in Chemistry, 2025)
IntroductionHeavy metal pollution poses significant food safety risks. To address this, a composite hydrogel composed of hydrotalcite and alginic acid was developed for adsorbing cationic heavy metal pollutants prevalent in food-related wastewater.MethodsThe composite hydrogel was synthesized via hydrothermal methods and chemically crosslinked with calcium ions. Its adsorption capacity for representative cationic pollutants (Cu2+, Zn2+, Pb2+, Cd2+, Mn2+) was evaluated using Atomic Absorption Spectrometry (AAS). Cr3+ and Cr(VI) were excluded due to their anionic speciation, incompatible with the hydrogel’s cation-targeted adsorption mechanisms. Adsorption experiments were complemented by isotherm fitting and kinetic analyses.ResultsThe composite hydrogel exhibited the highest affinity for Cu2+ with a maximum adsorption capacity of 325.73 mg/g, followed by Zn2+ and Pb2+ at 284.78 mg/g. The adsorption process conformed to the Langmuir isotherm model and pseudo-second-order kinetics.DiscussionThe composite hydrogel demonstrated significantly superior adsorption performance compared to individual hydrotalcite and alginate hydrogels. This enhanced capability indicates its promising potential for application in heavy metal remediation, particularly for mitigating food safety risks associated with cationic metal contaminants.